Studi Metaanalisis: Musik Untuk Menurunkan Stres - Mahargyantari P. Dewi (Faculty of Psychology, Universitas Gadjah Mada, 2009)
Music has been considered as a widespread social phenomenon recently. A meta‐analysis review of research articles using music to decrease stress was conducted on 20 quantitative articles, consisted 40 studies and involving 1555 participants. The participants in this research consisted from four to eighty years old. The result showed that music could decrease stress. However, this finding supports previous researches and further analysis revealed that music can improve aspects of stress, such as physical, behavior, and psychological.